Penjejak Pose Wajah Otomatis pada Sistem Pengenalan Wajah - Kartika Firdausy (Faculty of Engineering, Universitas Gadjah Mada, 2013)
Face recognition systems have been widely used in various security applications, for example in attendance system. The success of face recognition system relies on the trained face images as well as the face image captured that being recognized. Among the variables that determine the success of face recognition is face pose. Previous works showed that frontal face pose produced the best face recognition success rate. This paper proposes a face pose tracking sub system that can be used as a filter so that only the frontal face pose that will be processed in the face recognition sub system. The criteria for various face poses, i.e. frontal, tilted and turned, either left or right, have been formulated. Experimental results showed that the success rate of face pose recognition were between 64% up to 96%, with average of 84,7%.